The Effect of Financial Technology and Financial Literacy on the Sustainability of MSMEs in Lhokseumawe City with Financial Inclusion as a Mediating Variable - ., Ristati; ., Zulham; Akhyar, Chairil (Journal of Ecohumanism, 2024)
A related phenomenon is the lack of knowledge of the community as MSME actors to use financial technology in managing their businesses, while the development of financial technology is always growing. The focus of this study is to see how financial technology, financial literacy affect the sustainability of MSMEs with financial inclusion as a mediating variable. The research population is the number of MSMEs in Lhokseumawe City of 2,352 obtained from the Office of Cooperatives and MSMEs of Lhokseumawe City in 2023. the sample was determined by the slopin formula and selected using random sampling. The results showed that in testing the direct effect, there were three variables that had a direct influence or were said to have an effect, namely the financial literacy variable had an effect on the sustainability of MSMEs, financial inclusion had an effect on the sustainability of MSMEs and financial technology had an effect on financial inclusion. Meanwhile, financial technology variables have no effect on the sustainability of MSMEs and financial literacy has no effect on financial inclusion. In indirect testing, there is one mediated variable and one unmediated variable, namely the financial inclusion variable mediates the effect of financial technology on the sustainability of MSMEs, and the financial inclusion variable does not mediate the effect of financial literacy on the sustainability of MSMEs.